Market power in the German dairy supply chain - Aaron Grau (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2018)
The German dairy supply chain is one of the most important agrifood supply chains in Germany. In 2015, raw milk production accounted for 19.2% of the total domestic agricultural production value and dairy products summed up 8.0% of total German agrifood exports. Nevertheless, the economic success of the supply chain is overshadowed by reports on market power abused by dairies and retailers. Fueled by complaints of dairy farmers and dairies on non-competitive behavior of downstream supply chain agents, the German anti-trust agency conducted a sector analysis between 2008 and 2012. In its final report the anti-trust agency acknowledged the threat of oligopsony power at both markets, raw milk and dairy output market, but could not find any evidence. Thus, the main premise of the presented work is to empirically investigate the German dairy supply chain for the existence of oligopsony power at the raw milk and dairy product market. Three approaches, structure-conduct-performance paradigm (SCPP), new empirical industrial organization (NEIO), and asymmetric price transmission (APT), are revised and their suitability for the empirical application discussed. The theory review shows that none of the discussed approaches provide a model that fits the structure of the German dairy supply chain of oligopsonistic threat on two vertically integrated markets. Additional characteristics of the theoretical frameworks limit their suitability for the study further. Either the data requirements are high and the models highly complex, like in the case of NEIO, but an index of market power can be measured, or the data requirements are rather low and the theoretic models rather simple, like in the case of APT, but market power or its extent are not clearly identified. Consequently, a modification of one of the approaches is not sufficient and a new theoretical model merging aspects of NEIO and APT had to be developed. [...]
urn:nbn:de:gbv:3:2-94091
Keywords: 330